HBR's 10 must reads: The definitive management idears of the year from Harvard business review - Harvard Business School (Harvard Business Review Press, 2016)
HBR's Must reads series is the definitive collection of idears and best practices for aspiring and experienced leaders alike. These books offer essentical reading selected from the pages of Havard business review on topics critical to the success of every manager....